Upaya Meningkatkan Pembelajaran Literasi dan Numerasi di Lembaga Kesejahteraan Sosial Anak Bina Kasih Jl. Sei Terjun No 18.Medan Petisah - Gultom, Lois Enjelina; Siregar, Hairani; Ritonga, Fajar Utama (Medan Resource Center, 2023)
Numeracy literacy is the ability and knowledge to use various types of numbers and symbols related to basic mathematics. The aim of studying numeracy literacy for children, especially children from the Bina Kasih Orphanage, is to hone and strengthen students' numeracy knowledge and skills in interpreting numbers, data, tables, graphs and diagrams. The social work method uses the Group Work method with various stages, including: 1. Assessment Stage, 2. Planning Stage, 3. Intervention Stage, 4. Evaluation, 5. Termination Stage. The obstacles experienced when learning literacy and numeracy are that there are several participants from the Foster Love Orphanage who are not yet fluent in reading as well as multiplication. Therefore, there is literacy and numeracy learning at the Foster Love Orphanage which explains that learning is based on a literacy and numeracy learning model. provide a positive impact on the learning process, including being motivated, active and enthusiastic.